Synthesis and Reactivity of Cytotoxic Platinum(II) Complexes of Bidentate Oximes – A Step towards the Functionalization of Bioactive Complexes. Issue 14 (16th April 2018) - Belli Dell'Amico, Daniela; Colalillo, Marialuigia; Dalla Via, Lisa; Dell'Acqua, Martina; García‐Argáez, Aída N.; Hyeraci, Mariafrancesca; Labella, Luca; Marchetti, Fabio; Samaritani, Simona
Abstract : Two new platinum(II) complexes bearing triphenylphosphine and bidentate oxime ligands [Pt(Cl)(PPh3 ){(κ 2 ‐ N, O )‐(1{C(R)=N(OH)‐2(O)C10 H6 })}] (R = H, Me) were synthesized in good yields from trans ‐[PtCl(µ‐Cl)(PPh3 )]2 . The structure of [Pt(Cl)(PPh3 ){(κ 2 ‐ N, O )‐(1{CH=N(OH)‐2(O)C10 H6 })}] was determined by single‐crystal X‐ray diffraction. Both complexes showed good antiproliferative properties in vitro against HeLa, A2780, and A2780cis cancer cell lines. They reacted cleanly with alkylating agents in the presence of aqueous bases under phase‐transfer catalysis conditions to afford the corresponding O ‐alkylation products [Pt(Cl)(PPh3 ){(κ 2 ‐ N, O )‐(1{HC=N(OR′)‐2(O)C10 H6 })}] [R′ = CH2 CH2 Cl, CH2 Ph, (CH2 )4 Br] in good yields. Abstract : The complexes [Pt(Cl)(PPh3 ){(κ 2 ‐ N, O )‐(1{C(R)=N(OH)‐2(O)C10 H6 })}] (R = H, Me) are prepared. Both complexes are cytotoxic against HeLa, A2780, and A2780cis cancer cell lines. The complexes are cleanly alkylated by R′X in the presence of aqueous bases under phase‐transfer catalysis (PTC) conditions to afford the corresponding O ‐alkylation products in good yields.